Implementasi Nilai-Nilai Qur’ani dalam Membentuk Karakter Islami Santri di Lembaga Rumah Qur’an Nurul Jihad Atari Jaya (Aksiologi Pendidikan Tahfidz) - Mujiburrohman, Mujiburrohman; Rosyidah, Fahmi (Lembaga Yasin AlSys, 2026)
Although Qur’anic values have been widely discussed in previous studies, research that specifically highlights the role of Qur’anic values in shaping the Islamic character of santri, particularly in the Indonesian context, remains relatively limited. This study aimed to examine in depth the implementation of Qur’anic values in the formation of Islamic character at Lembaga Rumah Qur’an Nurul Jihad Atari Jaya, while also describing the history of the institution’s establishment, with a focus on how values in the philosophy of Islamic education, namely ubudiyah (servitude to Allah), khalifah (stewardship), ahsan (optimization of deeds), adil (justice), and mas’uliyah (responsibility), are actualized in learning strategies, curriculum management, and the formation of students’ Islamic character. A descriptive qualitative approach was employed, involving field observations of the tahfidzul Qur’an learning process and in-depth interviews with two tahfidz teachers and the head of the Rumah Qur’an institution. The findings show that the implementation of Qur’anic values at Rumah Qur’an Atari Jaya represents strong integration between the philosophy of Islamic education and the practice of Islamic character formation, thereby realizing an educational practice that is comprehensive, contextual, and transformative. These values function not only as a conceptual foundation in institutional documents but have also been internalized within a humanistic and spiritual learning culture oriented toward strengthening the Islamic character of santri. This study also opens up opportunities for further, more critical exploration of the implementation of Qur’anic values in character formation across diverse Islamic educational institutions.